Phenomenological Study of Elderly Quality of Life in Pandemic Covid-19: Phenomenological Study of Elderly Quality of Life in Pandemic Covid-19 - Zulfa Maulida Nadzir; Khanifa Fajria; Iffa Afia Amin Kitabi; Megawati Simanjuntak (Journal of Family Sciences, 2022)
Changes that occur during the pandemic COVID-19 greatly affect the quality of life of every individual, including the elderly. The elderly are one of the clusters most vulnerable to being exposed to a pandemic, which impacts the lives of the elderly. This study aims to analyze the phenomenon of the life of the elderly during the pandemic COVID-19. This research uses a qualitative approach with the type of phenomenological study that seeks to understand the meaning of events or symptoms as well as interactions with people or groups of people in certain situations. Although the results of this study found that the pandemic COVID-19 forced the elderly to have the ability to adapt to existing conditions, this adjustment affected the lifestyle of the elderly, especially in terms of health. Therefore, great attention to the elderly both from the elderly themselves, family support, and the surrounding environment is needed by the elderly in times of crisis, considering their characteristics are more at risk and to maintain the quality of life of the elderly.